Racist Ordering, Settler Colonialism, and edTPA: A Participatory Policy Analysis. (January 2016) - Tuck, Eve; Gorlewski, Julie
This article tells the story of an intervention by a collective of teacher educators on New York State's adoption of edTPA. Too often in education policy analysis, issues of race are discussed briefly, if at all. This article argues that attending to constructions of race specific to settler colonialism is an important approach to education policy analysis.